2002
DOI: 10.3354/meps233039
|View full text |Cite
|
Sign up to set email alerts
|

Biogeochemical processes in a small California estuary. 1. Benthic fluxes and pore water constituents reflect high nutrient freshwater inputs

Abstract: Elkhorn Slough, a small estuary in central California, receives nutrient inputs from agricultural and other non-point source runoff. To evaluate the effect of nutrient loading on ecosystem processes, rates of sediment oxygen consumption, benthic nutrient fluxes, pore water ammonium (NH 4 + ), dissolved inorganic phosphate (DIP) and sulfide (S 2 -) concentrations were measured at 5 sites several times each year between 1998 and 1999. Two sites near the head of the slough receive direct runoff from agricultural … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
28
0

Year Published

2004
2004
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 33 publications
(31 citation statements)
references
References 44 publications
(47 reference statements)
3
28
0
Order By: Relevance
“…4). Caffrey et al measured a benthic flux in APS as high as 8.6±2.9 mmol NH 3 m −2 day −1 , with concentration peaks at least one order of magnitude smaller than the concentration spikes seen in our data (Caffrey et al 2002b). Similar microcosm studies for nitrate have shown net negative benthic fluxes and indicate that the sediments in Elkhorn Slough can act as a sink for nitrate rather than a source.…”
Section: Carneros Creek Hudsons Landing East Carneros Creeksupporting
confidence: 52%
See 2 more Smart Citations
“…4). Caffrey et al measured a benthic flux in APS as high as 8.6±2.9 mmol NH 3 m −2 day −1 , with concentration peaks at least one order of magnitude smaller than the concentration spikes seen in our data (Caffrey et al 2002b). Similar microcosm studies for nitrate have shown net negative benthic fluxes and indicate that the sediments in Elkhorn Slough can act as a sink for nitrate rather than a source.…”
Section: Carneros Creek Hudsons Landing East Carneros Creeksupporting
confidence: 52%
“…The magnitude of this sink is on the order of −12 to −2 mmol nitrate m −2 day −1 depending on the sedimentary environment (K. Johnson, personal communication). A similar flux of −4.43±2.67 mmol NO 3 m −2 day −1 was measured in APS (Caffrey et al 2002b). While this sedimentary sink for nitrate could be contributing slightly to the decrease in concentrations seen at APC and APN, the magnitude is small and is not enough to be the primary mechanism accounting for the overall decrease seen postrestoration.…”
Section: Carneros Creek Hudsons Landing East Carneros Creekmentioning
confidence: 61%
See 1 more Smart Citation
“…1). Those results have been published separately in conjunction with nutrient and nitrification rate measurements from that site by Caffrey et al (2002Caffrey et al ( , 2003, who described sequence-analysis methods and results and their findings are related to the current study in 'Discussion' below.…”
Section: Methodsmentioning
confidence: 99%
“…In companion studies carried out over roughly the same time period as the Monterey Bay study reported here (Caffrey et al 2002, potential nitrification rates (measured in sediment slurries) and supporting measurements were made at monthly or slightly longer intervals at 5 sites in the slough. Although the slough sites varied amongst themselves in terms of their temporal variability, they all showed strong seasonal trends in temperature (Caffrey et al 2002) and increasing salinity (from nearly fresh in the spring up to 40 or 70, depending on site) in latesummer. Nitrification rates varied among sites and over time; maximum potential nitrification rates varied by up to 500-fold within a single site during the course of a year .…”
Section: Relationship Between Ammonium Oxidation Rates and Diversity mentioning
confidence: 99%